(3GdChQGO GddjdjIs - (3GdMGJej, GdWGFj, GHf YQHj, eMjj GdOjf, eMeO Hf Ydj Hf eMeO Hf YQHj, J(B638(3g`s
(3ChdgG (B:s
(3CfJ GdeMjW HZjH cd TGgO GdeSJhdj Ydi HGWf cd XGgQs
(3BNQgG (B:s
(3CfJ eScf GdSeGA heYde GdCSeGA dG Edg EdG CfJ GdhGMO GdaQO GdUeO GdPj de jdO hde jhdO hde jcf dg cahG CMO hUdi Gddg Ydi SjOfG eMeO TQa GdfHjjf hYdi Bdg hUMHg CLeYjfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 6 / 281s
(3eYLe GdeDdajf(B: 3 / 531s
(3cTa GdXfhf(B: 2 / 1261s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJUha hGdBOGH GdTQYjIs